ANALISIS VARIABEL YANG MEMPENGARUHI PROFITABILITAS PADA PERBANKAN UMUM TAHUN 2006 – 2009 - Ayu Intan Purnama Sari (Jurnal Ekonomi Pembangunan, 2014)
The study was a kind of descriptive quantitative research conducted on 16 banks, entitled "Analysis of the influence Profitability in Commercial Banking Go Public 2006-2009. This study aims to find out how much influence the Capital Adequacy Ratio, Asset utility, and total assets to profitability in the General Banking that go public in 2006-2009. This study, the authors take the hypothesis that there is in the expected significant effect between Capital adequacy ratio, Utility Assets, and Total Assets of Banking profitability in general which went public in 2006-2009. The analysis tools is to use a statistical test approach is called the test of significance, the decision to accept and reject Ho made on the basis of statistical values (t test and F test) obtained from the calculation is then compared with the value-free table at a certain degree. From the data analysis has been conducted simultaneously indicates that the variable Assets Utility has a more significant results on profitability (ROA) of the CAR variable, and total assets of profitability (ROA). This can be seen from the probability or significance level, namely the variable Capital Adequacy Ratio, Utility Assets, and Total Assets amounted to 0,7400; 0,0000; and 0,002708. It can also be seen from the F test, which Fcount > Ftable that is equal to 142,5 > 2.76.